Discriminant canonical analysis as a tool for genotype traceability testing based on turkey meat and carcass traits - Salgado Pardo, José Ignacio; González Ariza, Antonio; Navas González, Francisco Javier; León Jurado, José Manuel; Díaz Ruiz, Esther; Delgado Bermejo, Juan Vicente; Camacho Vallejo, María Esperanza (Frontiers in Veterinary Science, 2024)
The present work aims to develop a statistical tool for turkey breed traceability testing based on meat and carcass quality characteristics. To this aim, a comprehensive meta-analysis was performed collecting data from a total of 75 studies approaching meat and carcass attributes of 37 turkey strains and landraces since the late 60's. A total of 22 meat and carcass traits were considered as variables, grouped in the following clusters: carcass dressing traits, muscle fiber properties, pH, colorimetry, water-capacity traits, texture-related attributes, and nutritional composition of the meat. Once the multicollinearity analysis allowed the deletion of redundant variables, cold carcass weight, slaughter weight, muscle fiber diameter, sex-female, carcass/piece weight, meat redness, ashes, pH24, meat lightness, moisture, fat, and water holding capacity showed explanatory properties in the discriminating analysis (p < 0,05). In addition, strong positive and negative correlations were found among those variables studied. Carcass traits were positively associated, particularly slaughter weight and cold carcass weight (+0.561). Among meat physical traits, pH showed positive correlations with drip loss (+0.490) and pH24 (+0.327), and water holding capacity was positively associated with cholesterol (+0.434) and negatively with collagen (-0.398). Attending to nutritional traits, fat and ash showed a strong correlation (+0.595), and both were negatively associated with moisture (-0.375 and -0.498, respectively). Strong negative correlations were found as well between meat protein and fat (-0.460) and between collagen and cholesterol (-0.654). Finally, Mahalanobis distances suggested a clustering pattern based on meat and carcass characteristics that report information about interbreeding and varieties proximity. This study establishes a departure point in the development of a tool for breed traceability guaranteeing, aimed to enhance distinguished, local breed-based turkey meat.